Package Design for Children: Do Practitioners Get It Right? - Chareonsakdi, Thidarat (Auckland University of Technology, 2009)
The literature indicates that children are highly influenced by product packaging and that it is the packaging that will make the product stand out from the crowd and hopefully making a sale. There have been a number of valuable studies offering practitioners principles and guidelines on how to enhance package design for products that target children; however the extent to which practitioners adhere to the principles proposed by academics has had limited attention. This study is therefore aimed at examining the degree to which practitioners implement current knowledge relating to the principles of package design in the context of packages designed to attract children, while simultaneously assessing the relationship between package design and brand performance. An extensive secondary research of the literature has been made to establish a list of criterion for package design for children elements assessment. At the same time, attempts have been made to gather brand performance data. Product samples have been collected from major supermarkets in New Zealand and then analysed against the criterion using the principle of content analysis. The result generated by this study shows that practitioners are mostly adhering to the principles of children’s package design established by academic research. However, the relationship between brand performance and package design was not established in this study.
Keywords: Package design; Children; Marketing; Content analysis; Gap between theory and practice